Neighborhood-based argumental community support in the context of multi-topic debates - Coronel, Irene Milagros (2024)
The formal characterization of abstract argumentation has allowed the study of many exciting characteristics of the argumentation process. Nevertheless, while helpful in many aspects, abstraction diminishes the knowledge representation capabilities available to describe naturally occurring features of argumentative dialogues; one of these elements is the consideration of the topics involved in a discussion. In studying dialogical processes, participants recognize that some topics are closely related to the original issue; in contrast, others are more distant from the central subject or refer to unrelated matters. Consequently, it is reasonable to study different argumentation semantics that considers a discussion’s focus to evaluate acceptability. In this work, we introduce the necessary representational elements required to reflect the focus of a discussion. We propose a novel extension of the semantics for multi-topic abstract argumentation frameworks, acknowledging that every argument has its own zone of relevance in the argumentation framework, leading to the concepts of neighborhoods and communities of legitimate defenses. Furthermore, other semantic elaborations are defined and discussed around this structure.